2018
DOI: 10.1021/acs.jpclett.8b02349
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Defect Motions in Brittle Layered Sodium Titanate Nanowires

Abstract: In situ tensile tests show atypical defect motions in the brittle NaTiO (NTO) nanowire (NW) within the elastic deformation range. After brittle fracture, elastic recovery of the NTO NW is followed by reversible motion of the defects in a time-dependent manner. An in situ cyclic loading-unloading test shows that these mobile defects shift back and forth along the NW in accordance with the loading-unloading cycles and eventually restore their initial positions after the load is completely removed. The existence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…12−29 Experimental dynamic visualization of the structural evolution at the atomic scale can be realized using various in situ high-resolution TEM (HRTEM) deformation methods, 13,14,24,25 involving the use of specially designed TEM holders integrated with accessory platforms, such as push-to-pull (PTP) chips and bimetallic strips. 26,27 Alternatively, herein, we explored bending behaviors of individual ZnO NWs using a reported in situ HRTEM bending method. A colloidal thin film was used to induce the bending deformation directly, protecting NWs from damage and contamination during the NW manipulation and welding involved in the methods mentioned above.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12−29 Experimental dynamic visualization of the structural evolution at the atomic scale can be realized using various in situ high-resolution TEM (HRTEM) deformation methods, 13,14,24,25 involving the use of specially designed TEM holders integrated with accessory platforms, such as push-to-pull (PTP) chips and bimetallic strips. 26,27 Alternatively, herein, we explored bending behaviors of individual ZnO NWs using a reported in situ HRTEM bending method. A colloidal thin film was used to induce the bending deformation directly, protecting NWs from damage and contamination during the NW manipulation and welding involved in the methods mentioned above.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Various techniques have been developed to study nanomaterials’ mechanical properties, which commonly involve atomic force microscopy (AFM) and scanning/transmission electron microscopy (S/TEM). Experimental dynamic visualization of the structural evolution at the atomic scale can be realized using various in situ high-resolution TEM (HRTEM) deformation methods, ,,, involving the use of specially designed TEM holders integrated with accessory platforms, such as push-to-pull (PTP) chips and bimetallic strips. , Alternatively, herein, we explored bending behaviors of individual ZnO NWs using a reported in situ HRTEM bending method. A colloidal thin film was used to induce the bending deformation directly, protecting NWs from damage and contamination during the NW manipulation and welding involved in the methods mentioned above. ,, Unlike conventional ZnO NWs, the as-prepared wurtzite ZnO NWs inherit rich axial SFs lying in pyramidal I ( π 1 ) planes or prismatic planes introduced during the synthetic process.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium titanates are a suitable platform to either remove or deliver metals under physiological conditions and have previously been used in medical treatments, indicating their biosafety . Sodium titanate not only exhibits bioactive properties because of the presence of sodium ions but also possesses favorable mechanical properties such as high Young’s modulus (up to 250 GPa) . The surface properties of titanate substrates can be modified by conducting functionalization via bonding surface hydroxyl groups with an organic ligand.…”
Section: Introductionmentioning
confidence: 99%
“…21 On the other hand, because of the reduced material size, the differential of the defect quantity can result in fluctuating elastic moduli. 21,22 More intriguingly, it is found that during the deformation of NWs, the aggregation of dislocations can be mitigated so that amorphization or crack formation in the NWs can be hindered even with a large elastic strain. 16,23 In some other cases, mechanical energy can also be dissipated in strained lattices, which allows the NWs to withstand high deformation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Typically, the enhanced elasticity of NWs compared to their bulk counterparts is usually attributed to the size effect (increased surface atom ratio), , especially when the internal defects are scarce . On the other hand, because of the reduced material size, the differential of the defect quantity can result in fluctuating elastic moduli. , More intriguingly, it is found that during the deformation of NWs, the aggregation of dislocations can be mitigated so that amorphization or crack formation in the NWs can be hindered even with a large elastic strain. , In some other cases, mechanical energy can also be dissipated in strained lattices, which allows the NWs to withstand high deformation. , Nevertheless, the lattice shear accompanying deformation will be probably terminated by inelastic dislocation and/or other defect activities, such as twinning. Consequently, it is difficult to realize reversible lattice shear strain beyond 8% …”
Section: Introductionmentioning
confidence: 99%